Reforma powiatowa-zagadnienia prawnoustrojowe - Leoński, Zbigniew (Wydział Prawa i Administracji UAM, 1993)
The article contains the evaluation of basic assumptions of the draft law on provincial self-government as well as the considerations on various possibilities of the structural arrangement of local government on the provincial level. The starting point is here the evaluation of the fact that at a provincial level there are to be created self-governmantal entities only, and thus the influence of t he state governmental administration will be assured only to a limited extent. As to the territorial division, one has to assume that it will be a resultant of various tendencies. In the first place, it should be shaped so that it could implement its own tasks without the assistance of the state. The reform of the territorial division will entail the changes in the structure of specialized administrative bodies (e.g., courts or prosecutors' offices). Although the draft law refera to solutions applied at a commune (gmina) level, one should also take into account differences resulting from the tasks implemented by self-government bodies at a provincial level. With respect to the tasks, and especially the powers, the focus shifts here to the substantive law located outside the scope of the Law on Territorial Government. However, the reform will make it indispensable to amend both the latter law as well as the substantive law (and the administrative law in particular).
The districts'reform -legal and structural problems